Transformation of Surabaya Scout Headquarters Toward a Modern Image - Seftavia Candra Kirana; Febby Rahmatullah Masruchin (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
The Surabaya Branch Scout Council Headquarters serves as the center for administration, training, character development, and scouting activities at the city level. However, the existing facility faces several challenges, including limited space capacity, lack of spatial flexibility, ineffective circulation, and a building image that no longer reflects the needs of contemporary scouting activities. This study aims to analyze the redesign needs of the Surabaya Scout Headquarters and develop a design concept that supports functional optimization while strengthening the identity of the Scout Movement. The research employs a qualitative descriptive method through site observation, documentation, literature review, and comparative studies. The findings indicate the need for increased spatial capacity, flexible multifunctional spaces, improved zoning and circulation systems, and a stronger architectural identity. Based on these findings, the concept of “Future Scout New Image” is proposed through the application of the Coconut Shoot Metaphor Architecture approach. The redesign is expected to create a modern, representative, adaptive, and recognizable Scout Headquarters that supports the development of future generations.